Kalanchoe dissecta (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae), a new species from South Africa, published as K. rotundifolia f. tripartita in 1978 and proposed but not validly published as “K. rotundifolia var. tripartita” in 1956 - Smith, Gideon F. (Phytotaxa, 2026)
Kalanchoe dissecta (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae) is described for material from eastern South Africa. The species shares similarities with K. rotundifolia under which it was previously proposed—but not validly published—at the rank of varietas, as “K. rotundifolia var. tripartita” (in 1956), and at the rank of forma, as K. rotundifolia f. tripartita, a combination that was validly published (in 1978). Kalanchoe dissecta differs from K. rotundifolia in vegetative and reproductive characters. At maturity, the leaves of K. dissecta are variously laterally lobate, while those of K. rotundifolia, as the name was epitypified, lack marginal lobes. The new species fits in K. ser. Rotundifoliae, which includes small, generally low-growing, shrubby species with variously urceolate, orangey or reddish flowers that show distinct diurnal movement, and with the flowers becoming tightly twisted post-anthesis.